Pemanfaatan Kompos Daun Bambu yang Melimpah untuk Peningkatan Taraf Ekonomi Masyarakat Melalui Budidaya Tanaman Hortikultura di Desa Marga Asih, Kecamatan Cicalengka, Kabupaten Bandung - Dwi Susanto; Suli Suswana; Lilis Irmawatie; Dick Dick Maulana (LPPM UNINUS, 2022)
The impact caused by the COVID-19 pandemic was really experienced by the community and farmers in Margaasih Village, Cicalengka District, Bandung Regency. Efforts are needed to mitigate these negative impacts, especially in terms of the economic and health aspects by utilizing the available resources and opportunities. This community service program aimed to meet these needs, with three activities, namely by: (i) utilizing the abundant bamboo leaf wastes in their village; (ii) taking advantage of opportunities to meet the demand for grapes that are always imported from abroad; and (iii) optimizing their usual farming activities by introducing okra as a new vegetable that is not widely known by the public. These three activities have been carried out in Margaasih Village with a very positive response from them. They felt they got new knowledge and insights about things they have not done before. The bamboo leaf wastes that have been unutilized before can finally be turned into high-value compost. Grape plants could be cultivated by farmers in their lands. The productivity of the agricultural lands can still be increased, i.e, by cultivating okra which has a high economic value. With these three efforts, we hope that farmers can increase the productivity of their farming businesses which in turn can increase their income and welfare.